SOSIALISASI PENGEMASAN KULINER LOKAL DESA MONANO KABUPATEN GORONTALO UTARA - dwi cahyani; A. Fahmi Indrayani (LP2M IAIN Sultan Amai Gorontalo, 2023)
As one of the villages with potentially bustling tourist visiting, it would certainly be an excellent capital for Monano's village to be able to support the economic growth of the people. One of the sectors that has an excellent potential for improving the economy is the small and medium-size micro enterprises (UMKM) of the Monano's village community especially for local food production. Most UMKM actors in Monano Village only use a small amount of packaging without the labels of products and pay little attention to the essential ingredients of the packaging that keep the product going. The socialization was held about the local culinary packaging to solve this problem. The method which used is the socialization and the direct stakeholder of UMKM who produces local food products in Monano village. The result of this activity is the enhancement of people's understanding of UMKM which involved in Monano village and confirmed by the improvement of the local food supply and the label production from three UMKM in Monano village, and the results of correction survey on packaging and label showed that the respondent interested to the result of packaging product. Keywords: Packaging Desain; Label; Umkm; Monano Village